Analisis Perancangan Mesin Pencacah Limbah Plastik Menggunakan Pisau Crusher dan Shredder - Ustman Khomsaha Shofwan; Joko Waluyo*; Taufiq Hidayat (Jurnal Teknologi, 2023)
Waste in the form of garbage in the Piyungan area, Bantul Regency, consists of organic and non-organic waste, currently the condition is increasingly worrying because the landfills are very limited, so waste management must be managed optimally. To reduce the accumulation of excessive waste, a waste-cutting machine is needed. An efficient waste-cutting machine requires the right knife by choosing a knife between the crusher and shredder types. The selection of one of the blades used in the waste-cutting machine requires a design analysis using FEA (Finite Element Analysis) calculations and simulation assistance. Based on the results of the analysis of the calculation of the crusher-type knife using 4 blades, the required power is 2 HP, costs 8.8 million rupiahs and, the results of the FEA allowable stress test are 3.19E + 04, and 2.5 E + 08 are safe. While the Shredder type blade uses 13 blades, the required power is 2 HP, which costs 9.8 million rupiah and the FEA allowable stress test results are 1.53E+04 and 2.5E+08 safe. The results of the analysis obtained are that the selected crusher-type knife can be recommended for use in the design of a waste chopping machine because the manufacturing cost is 8.8 million and the Allowable stress is 3.19E+04,